2007
DOI: 10.1016/j.virol.2006.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal sequence exchange between non-retro viruses and hosts leading to the appearance of new host phenotypes

Abstract: Divergence among individuals of the same species may be linked to positional retrotransposition into different loci in different individuals. Here we add to recent reports indicating that individual variance occurs due to the integration of non-retroviral (potyviral) RNAs into the host genome via RNA recombination followed by retrotransposition. We report that in bees (Apis mellifera), approximately 30% of all tested populations carry a segment of a dicistrovirus in their genome and have thus become virus-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 35 publications
4
78
0
1
Order By: Relevance
“…Several of these gene transfer events can be clearly attributed to retrotransposon activity (Ballinger et al 2012), and in at least one case the gene transfer is associated with viral resistance (Maori et al 2007). We hypothesize that, lacking RNA-dependent RNA-polymerases used to amplify RNAs for viral silencing in organisms for which this function is well-established (Baulcombe 2004;Rechavi et al 2011), some metazoans could use a multistep process: reverse transcription of viral transcripts followed by RNA polymerization templated on viral complementary DNA (cDNA).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these gene transfer events can be clearly attributed to retrotransposon activity (Ballinger et al 2012), and in at least one case the gene transfer is associated with viral resistance (Maori et al 2007). We hypothesize that, lacking RNA-dependent RNA-polymerases used to amplify RNAs for viral silencing in organisms for which this function is well-established (Baulcombe 2004;Rechavi et al 2011), some metazoans could use a multistep process: reverse transcription of viral transcripts followed by RNA polymerization templated on viral complementary DNA (cDNA).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown recently that nucleotide sequence fragments coding for viral RNA can be inserted into the bee genome (Maori et al, 2007). This was demonstrated for Israeli acute bee paralysis virus (IAPV), a member of the Dicistroviridae family.…”
Section: Discussionmentioning
confidence: 99%
“…In this hypothetical case, the PCR signals of our assay could be derived from sequences embedded in the bee genome. However, the sequence fragments described by Maori et al (2007) came from a distant region downstream of the Rd Rp region. To confirm the non-existence of sequence exchange and the amplification from viral matter alone, additional experiments will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…IAPV analyses were carried out as described previously (Maori et al, 2007) in the virus laboratory of Hebrew University of Jerusalem (Israel). The presence of f ipronil and imidacloprid in stored pollen were carried out as described previously (Jiménez et al, 2007;Higes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…IAPV was first described in Israel (Maori et al, 2007) and it was associated with bee mortality, even though only some hives in an apiary were affected. It was suggested that genetic diversity among honey bees could explain the different susceptibility/resistance Honeybee colony loss in Spain 659 between hives in an apiary.…”
Section: Introductionmentioning
confidence: 99%